2008
DOI: 10.2217/17520363.2.4.363
|View full text |Cite
|
Sign up to set email alerts
|

Tau as a Biomarker of Neurodegenerative Diseases

Abstract: The microtubule-associated protein Tau is mainly expressed in neurons of the CNS and is crucial in axonal maintenance and axonal transport. The rationale for Tau as a biomarker of neurodegenerative diseases is that it is a major component of abnormal intraneuronal aggregates observed in numerous tauopathies, including Alzheimer's disease. The molecular diversity of Tau is very useful when analyzing it in the brain or in the peripheral fluids. Immunohistochemical and biochemical characterization of Tau aggregat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
64
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(64 citation statements)
references
References 196 publications
(226 reference statements)
0
64
0
Order By: Relevance
“…Most frequently, these studies served to characterize post-translational modifications within tau (50 -53) and/or explored the merits of tau as a biomarker for neurodegenerative disease (54,55). Conceptually more similar to the current study were prior investigations that identified proteins that copurify with microtubules (56), explored the composition of neurofibrillar tangles (57), or investigated how the presence or absence of methylene blue alters the tau-associated proteome (58).…”
Section: Discussionmentioning
confidence: 96%
“…Most frequently, these studies served to characterize post-translational modifications within tau (50 -53) and/or explored the merits of tau as a biomarker for neurodegenerative disease (54,55). Conceptually more similar to the current study were prior investigations that identified proteins that copurify with microtubules (56), explored the composition of neurofibrillar tangles (57), or investigated how the presence or absence of methylene blue alters the tau-associated proteome (58).…”
Section: Discussionmentioning
confidence: 96%
“…CSF phospho-tau is thought to reflect phosphorylation states of tau in the brain [6,30,67]. While CSF p-tau181 has been widely used in CSF biomarker studies, other p-tau epitopes such as p-tau199, p-tau231, p-tau404 are also increased in AD patients [6,30,67]. A study comparing p-tau181, p-tau199, and p-tau231 using the same samples shows similar discrimination between AD and control [6,31].…”
Section: Discussionmentioning
confidence: 99%
“…There are up to 85 identified phosphorylation sites on the longest Tau isoform and numerous sites are associated with Tau dysfunction and neurodegeneration (Schraen‐Maschke et al . ; Wang et al . ).…”
Section: Discussionmentioning
confidence: 99%